(3JMaI GdNd GdhOhO aj eYQaI GdVhGHW hGdMOhOs - (3eMeO GdbOSj GdTGaYj, CHh MGeO,J (B893 (3g` s ((3GdbGgQI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Yde GdEfSGf eGde jYdehHYO abO QCjJ ai TgQ ThGd Cf CTY dWdHI gPG GdYUQ GdeTJZdjf Hafhf GdYde CdaGX JTJed Ydi bhGYO hVhGHW s
(3BNQgG (B:s
(3hgPg GdebhdGJ TGedI dLejY GdehLhOGJ GdeecfI hGddg JYGdi GYde HGdUhGH Je GdcJGH hGdMeO ddg s
(3GdfSNI HgG MhGTs
(3Ydjg JedcGJs
(3fbdJ ef fSNI GdeDda GdecJhHI HNWg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdeYGQa GdYGeIs